Non-destructive testing of train axle using ultrasonic phased arrays - Lee, Lawrence Boon How (2018)
The ever increasing railway transport demand results in higher stress and damages to the train vehicles components, particularly the train axles. To ensure smooth and efficient railway transport operations in the such demanding situations, demand for shorter and effective train axle inspection is desired. This gives rise to the utilisation of Phased Arrays Ultrasonic techniques in the inspection process. However, as phased arrays are considered one of the more advanced technique in the Ultrasonic NDT field, it faces a bottle-neck situation. One way to overcome this bottle-neck is the automation phased array inspection process of train axle. This paper will focus on the use of phased array technology on train axle inspection and the development of automated phased array inspection tool prototype. The author will employ phased array ultrasonic technique to identify target defects on train axle. In addition, the author will fabricate a few probe holders for the automated hardware inspection tool and experiment trials will be conducted to decide on which probe holder design is suitable for the automation inspection application. It is crucial that the train axle inspection process continue to evolve with the development of automation phased array inspection. A well developed automatic phased array inspection tool will greatly reduce inspection time and enhance inspection procedure while maintaining the high accuracy in detecting defects on train axles.